The Link Between Periodontal Hygiene Status and Pregnancy: Awareness and Understanding Among Iraqi Pregnant Women - Athraa Ali Mahmood; Banaz Jabbar Ali; Ban Karem Hassan (International Journal of Dentistry)
Conclusion: The findings of this investigation supported the need for interaction between dental practitioners and gynecologists, including routine dental checkups during antenatal visits of pregnant women, as essential to develop and improve the habits of awareness of the need for periodontal hygiene during pregnancy. Furthermore, there was a significant association between educational level and awareness and knowledge among pregnant women about the relationship between periodontal health and pregnancy.